2019
DOI: 10.3390/ijerph16061063
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s Important to Make Changes.’ Insights about Motivators and Enablers of Healthy Lifestyle Modification from Young Aboriginal Men in Western Australia

Abstract: Lifestyle modification can improve the health of people with or at risk of non-communicable diseases; however, initiating and maintaining positive health behaviours including healthy eating and physical activity is challenging. Young remote Aboriginal people who had successfully made significant healthy lifestyle changes were sought out to explore how they achieved this success. Four Aboriginal men aged 20–35 years were identified and consented to participate. Their perceptions of motivation for change, strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…A lack of knowledge and education associated with diabetes can increase the risk of undiagnosed cases, illness progression and comorbidities through lack of screening and detection. However, this can be overcome through increased knowledge and changes in health beliefs that support healthy lifestyle changes, as found in this study and others 39 …”
Section: Discussionmentioning
confidence: 72%
“…A lack of knowledge and education associated with diabetes can increase the risk of undiagnosed cases, illness progression and comorbidities through lack of screening and detection. However, this can be overcome through increased knowledge and changes in health beliefs that support healthy lifestyle changes, as found in this study and others 39 …”
Section: Discussionmentioning
confidence: 72%
“…All 11 included studies were published between 2010 (Abbott et al, 2010;Foley, 2010) and 2019 (Brown et al, 2019;Seear et al, 2019). Three studies were conducted in the Australian State of Queensland (Brown et al, 2019;Foley, 2010;Sushames et al, 2017), two each in Western Australia (Nilson et al, 2015;Seear et al, 2019), and South Australia (Canuto et al, 2013;Tsourtos et al, 2014) and one each in New South Wales (Abbott et al, 2010), and the Northern Territory (Thompson et al, 2013) and a statutory authority of Australia called the Torres Strait Islands (Macniven et al, 2018). Additionally, one study was conducted across four Australian States-Victoria, Western Australia, South Australia, and New South Wales (Chapple et al, 2016).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Additionally, one study was conducted across four Australian States-Victoria, Western Australia, South Australia, and New South Wales (Chapple et al, 2016). Six studies (Brown et al, 2019;Chapple et al, 2016;Macniven et al, 2018;Nilson et al, 2015;Seear et al, 2019;Thompson et al, 2013) reported that they were conducted in remote Indigenous communities. The data collection methods for the 11 included primary studies were via interviews (semi-structured and unstructured) individually or focus groups (often referred to in the Indigenous communities as yarning groups).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations